Exploration of the Implications of the Spiritual and Islamic Akhlaq Paradigm on Earnings Management - Irmawati Irmawati; S. Syarifuddin; A. Alimuddin; Hikma Niar (Manunggal Halim Jaya, 2026)
This study explores the implications of the Islamic spiritual paradigm and akhlaq on earnings management practices. Grounded in the values of shiddiq (truthfulness), amanah (trust), ‘adl (justice), and maslahah (public interest), the research highlights how Islamic principles serve as a normative framework for ethical financial reporting. Using a descriptive qualitative method through library research, the study analyzes secondary sources, including academic journals, Qur’anic verses, and hadiths, to understand how spiritual values discourage earnings manipulation. Findings show that both accrual-based and real earnings management contradict Islamic teachings by distorting financial information and violating the trust of stakeholders. The concepts of hisab (accountability) and niyyah (intention) provide internal moral controls, encouraging transparency and honesty in financial practices. Furthermore, the application of maqasid shariah, particularly hifz al-maal (protection of wealth), strengthens ethical awareness and promotes organizational conduct aligned with justice and sustainability. This study contributes to the literature by offering an Islamic ethical lens on earnings management, advocating for a culture of professionalism rooted in spiritual consciousness and moral responsibility.